Improving Students' Motor Skills, Competency and Sportsmanship with a Cooperative Learning Approach to Floor Gymnastics Materials - Muhammad Arkanul Arba'; Suwardi Suwardi (International Journal of Experimental Sports Science Research, 2025)
Background: Motor Skill Competency and sportsmanship are two essential outcomes of physical education learning that contribute to students' physical development and character formation. However, many students still demonstrate limited mastery of floor gymnastics skills and insufficient sportsmanship behaviors during learning activities. Cooperative Learning is considered an effective instructional approach because it promotes active participation, peer interaction, collaboration, and shared responsibility among students. Nevertheless, empirical evidence examining its simultaneous effect on Motor Skill Competency and sportsmanship in floor gymnastics learning remains limited. Objectives: This study aimed to analyze the effectiveness of the Cooperative Learning approach in improving Motor Skill Competency and sportsmanship among students during floor gymnastics learning. Methods: This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The participants consisted of 36 junior high school students selected through purposive sampling. The intervention was conducted over eight weeks using the Cooperative Learning approach in floor gymnastics lessons. Motor Skill Competency was assessed through performance-based evaluations covering balance, coordination, flexibility, body control, and movement technique, while sportsmanship was measured using a validated questionnaire. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and Paired Sample t-Test at a significance level of α = 0.05. Results: The findings revealed significant improvements in both Motor Skill Competency and sportsmanship following the intervention. Motor Skill Competency increased from 67.42 ± 7.63 to 82.51 ± 6.38, representing a 22.38% improvement (p = 0.000). Sportsmanship scores increased from 70.18 ± 6.92 to 84.67 ± 5.81, representing a 20.64% improvement (p = 0.000). The largest improvement in Motor Skill Competency was observed in movement technique, while teamwork demonstrated the highest increase among sportsmanship indicators. Conclusions: The Cooperative Learning approach significantly improves both Motor Skill Competency and sportsmanship in floor gymnastics learning. These findings indicate that Cooperative Learning is an effective pedagogical strategy for simultaneously enhancing students' motor performance and positive social behaviors in physical education settings.